HLA-B*58:01 for Allopurinol-Induced Cutaneous Adverse Drug Reactions: Implication for Clinical Interpretation in Thailand - Sukasem, Chonlaphat; Jantararoungtong, Thawinee; Kuntawong, Parnrat; Puangpetch, Apichaya; Koomdee, Napatrupron; Satapornpong, Patompong; Supapsophon, Patcharin; Klaewsongkram, Jettanong; Rerkpattanapipat, Ticha (Frontiers in Pharmacology, 2016)
Background: The aim of this study was to investigate the predisposition to different types of allopurinol-induced cutaneous adverse drug reactions (CADR), including Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN; SJS-TEN, n = 13), drug reaction with eosinophilia and systemic symptoms (DRESS, n = 10) and Maculopapular eruption (MPE; n = 7), conferred by HLA-B*58:01 in a Thai population. Methods: This case-control association study compares 30 patients with allopurinol-induced CADR, allopurinol-tolerant control patients (n = 100), and a Thai general population (n = 1095). Patients' human leukocyte antigen type B (HLA-B) alleles were genotyped by using a two-stage sequence-specific oligonucleotide probe system. Results: Of a total 30 patients with CADR due to allopurinol, 29 (96.7%) patients were found to be at least heterozygous for HLA-B*58:01, compared to only 4.0% in allopurinol-tolerant patients (p < 0.001). Odds ratio (OR) for the association of HLA-B*58:01 with allopurinol-induced CADR in this population was 696.0 (95% CI: 74.8–6475.0). The HLA-B*58:01 allele was present in all patients with allopurinol-induced SJS-TEN (OR = 579.0, 95%CI: 29.5–11362.7, p < 0.001) and DRESS (OR 430.3, 95%CI: 22.6–8958.9, p < 0.001). Additionally, OR of HLA-B*58:01 was highly significant in the allopurinol-induced MPE patients (OR 144.0, 95%CI: 13.9–1497.0, p < 0.001). Conclusion: In this study we confirmed the association between HLAB*58:01 and allopurinol-induced SJS-TEN in a Thai population. In addition, we identified an association between HLA-B*58:01 and allopurinol-induced DRESS and MPE in this population. Therefore, HLA-B*58:01 can be used as a pharmacogenetic marker for allopurinol-induced CADR including SJS-TEN, DRESS and MPE. These results suggest that screening for HLA-B*58:01 alleles in patients who will be treated with allopurinol would be clinically helpful in preventing the risk of developing CARD in a Thai patients. Summary Regardless of phenotype, this is the first pharmacogenetic study of allopurinol-induced CADR in patients of Thai ancestry. In this study we confirmed the association between HLA-B*58:01 and allopurinol-induced SJS-TEN, DRESS, and MPE in Thai population. Regarding to our findings, the pharmacogenetic interpretation could be generalized to drug hypersensitivity including DRESS, SJS-TEN, and MPE.